Leadership in participatory modelling – Is there a need for it?. (November 2020) - Hämäläinen, Raimo P.; Miliszewska, Iwona; Voinov, Alexey
Abstract: The concept of leadership is introduced into the context of participatory modelling. Different leadership paradigms are described. The role of the modeler and the question who should be assigned the leadership role is analyzed. The leadership and management perspectives are compared. The leadership function assumes seeing the big picture and setting the right goals. Leadership is essential in guaranteeing responsible practices and the overall effectiveness of a project. This includes transparent, ethical and bias-aware modelling, resource planning and addressing challenges related to the changing project conditions as well as to sensitivity to social dynamics and stakeholder engagement. The paper suggests that there are clear benefits in taking the leadership perspective. Highlights: It is important to consider the leadership function in participatory modelling. Leadership styles can be different ranging from laissez-faire to systems leadership. Leadership role helps to keep in mind the big picture, overall goals and efficiency. Responsible and ethical practices are in the focus of a leader. Stakeholder engagement and project leadership require people skills.